مضامين ومميزات الشبكة البرامجية الرمضانية التيليفزيونية لقناة الخاصة شروق tv - صبرينة عمايدية; د/ذهبية آيت قاسي (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة : • تهدف دراستنا الى الاجابة عن الإشكالية التالية : ماهي مضامين ومميزات الشبكة البرامجية الرمضانية لقناة التلفزيونية الخاصة الشروق TV خلال شهر رمضان 1444ه \2023م؟ • قد تفرعت إلى جملة من التساؤلات • ما هي طبيعة البرامج التي ركزت عليها قناة الخاصة الشروق TV خلال شهر رمضان 1444ه\2023م ؟ • هل تتطابق مضامين البرمجة الرمضانية لقناة التلفزيونية الخاصة الشروق TV مع طبيعة شهر رمضان؟ • ما هي اهم المواضيع التي عالجتها الشبكة البرامجية الرمضانية القناة التلفزيونية الخاصة شروق TV؟ • ما هو حجم المساحة الزمانية للاشهار مقارنة مع باقي البرامج المقدمة عبر الشبكة البرامجية الرمضانية لقناة التلفزيونية الخاصة شروق TV خلال شهر رمضان1444ه\2023م؟ اعتمدنا في دراستنا على المنهج مسح بالعينة و تندرج دراستنا ضمن الدراسات الوصفية التحليلية كما اعتمدت على اداتين و هم الملاحظة و تحليل محتوى الشبكة البرامجية الرمضانية لقناة الخاصة الشروق TV و تمثلت عينة دراستنا في الشبكة البرامجية الرمضانية التلفزيونية لقناة الخاصة الشروق 1444ه \2023م و لقد وصلنا في نتائج التالية نذكر منها ما يلي : - استغلت قناة الشروق TV خلال شهر رمضان لزيادة عدد مشاهديه من خلال تقديم عدة منتوجات جديدة و اعمال جديدة و متنوعة لجذبهم إليها و كسبها لتاييدهم - اهم ما لاحظنا كذلك ان قناة الشروق TV ركزت بشكل كبير على الإشهارات حيث تنوعت اشهاراتها و كثرت فيوجد ازيد من 20 نوعا من الإشهارات حيث خالفة قانون الإشهار الشي ينص انه لا يتجاوز الإشهار 6 دقائق في ساعة بل تعدي الامر الى ساعة كلها إشهار الإطار القانوني الذي وضعته الشروق TV هو ان القناة تقدم نشرة اخبار فنلاحظ من خلال شبكتها البرامجية انها لا تحتوي على أي نشرة اخبار و انها بعيدة الكل البعد على تغطية ما يحدث و نقلها بصفة حصرية حيث انها ركزت على الأعمال الدرامية بمختلف اشكالها فقط . Abstract : My study stems from the following problem: How did Al-Shorouk TV deal with its TV program network during the first 15 days of Ramadan? Where my study aims to a set of goals, including the following: - This study aims to know the nature of the programs that Al-Shorouk TV focused on during Ramadan for the 2023 season. - It also aims to find out the extent to which the contents of the programs presented on Al-Shorouk TV correspond to the nature of virtue poetry - It aims at the most prominent and important topics that Al-Shorouk TV focused on during the month of Ramadan 2023. - Also, this study aims to know the importance of advertising within the media institution, especially within Al-Shorouk TV, and the most important periods that were divided for advertisements within the TV program network of Al-Shorouk TV channel during the month of Ramadan 2023. In order to achieve the aforementioned goals, it relied on a content analysis approach, which was included in the descriptive analytical studies. It also relied on two tools, namely content analysis and observation. The sample of my study was the TV program network of Al-Shorouk channel for Ramadan 2023 And we have reached the following results, including the following: - Al-Shorouk TV took advantage of the month of Ramadan to increase the number of its viewers by presenting several new products and new and diverse works to attract them and gain their support. - The most important thing we noticed as well is that Al-Shorouk TV focused heavily on advertisements, as its advertisements varied and increased, and there are more than 20 types of advertisements, as they violated the advertisement law, which stipulates that advertising does not exceed 6 minutes in an hour, but rather extends to an hour, all of which are advertisement - The legal framework set by Al-Shorouk TV is that the channel presents a news bulletin, so we notice through its program network that it does not contain any news bulletin and that it is far from covering what is happening and transmitting it exclusively, as it focused on dramas in all its forms only. - We also noticed a great diversity in religious programs, due to the nature of the blessed month, in which religious rituals are practiced abound, but what was strange is that the various religious programs were produced by foreigners.
دراسة وصفية تحليلية لشبكة رمضان 2023-1444